Foreign Direct Investment in ASEAN Airline Industry - Christiawan, Rio; Zuan, Haris; Jusoh, Sufian; Nugraha, Ridha Aditya (Faculty of Law, Hasanuddin University, 2024)
The development of aviation market in Southeast Asia after the Covid-19 pandemic is promising. More aircraft are delivered to the Asia-Pacific region, including the Association of South East Asian Nations (ASEAN) Member States. The introduction of ASEAN Open Skies (also known as ASEAN Single Aviation Market) a decade earlier together with ASEAN Economic Community Blueprint 2025 goals for an integrated and cohesive regional economy highlight the importance of a seamless air connectivity. Liberalisation of the airline industry in ASEAN Member States is crucial to restart the airline industry pre-pandemic and to grasp the so-called Asian century momentum. However, ASEAN Member States are reluctant towards liberalisation efforts, maintaining protectionism on both freedoms of the air (traffic rights) as well as foreign direct investment (ownership and control). Existing legal framework at regional level, namely ASEAN Framework Agreement on Services (AFAS) and ASEAN Trade in Services Agreement (ATISA), only received lukewarm attention from ASEAN Member States. This article discusses the urgency to recall the commitment of a gradual liberalisation based on AFAS and ATISA among the ASEAN Member States, the implementation of which will lead to the establishment of a regional community carrier which benefits ASEAN citizens.